A Computerized Health Hazard Appraisal System (CHAMP) - Laszlo, C. A.; Varga, L. E. (Methods of Information in Medicine, 1981)
Health Hazard Appraisal (HHA) is a technique providing quantitative assessment of health risks assumed by individuals. This paper describes the structure and operation of CHAMP, a modularized computer package designed for widespread use of HHA. Thus its design incorporates stringent criteria which include flexibility, expandability, adaptability to varied populations, error corrective capability, and low-cost operation. The experience with CHAMP in service has been excellent.
Keywords: Health Hazard Appraisal; Prospective Medicine; Computerized System; Lifestyle Improvement; Health Counselling